Investigation of the modulatory role of bulgarian Mentha piperita l. oil against radiation-induced oxidative disorders and antioxidant status in vitro - Y. D. Karamalakova (Trakia Journal of Sciences)
This investigation report on the free radical-scavenging and radio-modulatory properties of Bulgarian M. piperita L. oil. The chemically pure oil (97 %) was tested alone and after expositer to ultraviolet radiation (290-320 nm) and gamma radiation at doses of 5, 10, 20 and 30 Gy. The in vitro antioxidant status studied by different spectrophotometrically methods of M. piperita alone was found to be lower compared to UVB and 10 Gy radiated oil. By direct EPR spectroscopy, single almost symmetrical EPR signals were registered in oil alone (g= 2.00492 ± 0.0003), UVB (g= 2.00586 ± 0.0002) and 10 Gy irradiated (g= 2.0019 ± 0.0002) samples. Antioxidant activity and radical scavenging capacity of M. piperita oil alone and after radiation was also evaluated by the DPPH test. The intensities of the EPR signals of M. piperita oil alone, and irradiated samples demonstrated the possible formation of stable radical structures. The EPR spectra considerably higher after radiation, and excellent DPPH scavenging capacity exhibited by M. piperita indicate good antioxidant potential, radio-modulatory activity and prevent effectively radiation–induced oxidative disorders.